Non-time-loss and time-loss softball injuries in secondary school athletes: A report from the National Athletic Treatment, Injury and Outcomes Network (NATION) - Snyder, A. R.; Huxel Bliven, K. C.; Gibson, A.; Simon, J.; Dompier, T. P.; Wasserman, E. P.; Rynard, K. L.; Kerr, Z. Y. (Journal of Athletic Training, 2020)
Context: Most studies of injury trends associated with softball focus on injuries requiring at least 24 hours of missed participation time (time-loss [TL] injuries), with little focus on those that do not (non-time-loss [NTL] injuries). A better understanding of injury trends associated with softball will improve athlete care.